Sustainable Approach of Generating Water and Energy: Techno-Economic Analysis of a Hybrid Solar Photoactive Thermal System Coupled with Direct Contact Membrane Distillation for Water Purification and Electricity Generation - Fahad Awjah Almehmadi; Abdullah Najib; Emad Ali; Hany Al-Ansary; Jamel Orfi (Applied Sciences, 2022)
Cogeneration of energy and clean water by incorporating direct contact membrane desalination (DCMD) and photovoltaic hybrid thermal system (PVT) into a residential building is a promising technology for addressing water and energy shortage in distant places. In this study, a microgrid integration between PVT, DCMD, and a residential building is proposed, with an end goal to meet partial electric load in the building and provide a clean water supply. A mathematical model was developed and validated to assess the system’s performance. Artificial Neural Network (ANN) and optimization techniques have been used. The performance of the proposed system was studied under the meteorological conditions of Riyadh, Saudi Arabia, and under several design and operation parameters. The optimal performance of the system is found as functions of the inlet brackish water temperature to the PVT, capital and installation cost, and the desired water productivity. Results reveal that the specific cost of water (SCW) is 23.6 $/m3 achieved with a renewable energy penetration of 25%, depending on the cost of PVT and electricity price. Thus, the proposed system meets 25% of the electric demand for the residential building, while the rest is imported from the grid. In addition, the proposed system reduced the annual greenhouse gas emission by 4300 kg for a single building. This study will contribute to a better understanding of incorporating innovative clean energy and water systems such as PVT and DCMD into a residential house.